Mesh for pelvic prolapse: the bad guy? - Álvarez Garzón, Horacio Joaquín (2016)
With more understanding on determinants of successful outcomes in patients, we also find that mesh contribution is not so important as initially thought as it may increase risks and complications. After reviewing records, the FDA warned first in 2008 and then in 2011 and 2013 that complications with use of mesh were not infrequent. Current tendency is to create multinstitutional registries to obtain both anatomical subjective information and results in quality of life, as well as to register complications and their treatments. Absorbable mesh is associated with fewer perception of the prolapse symptoms and fewer operations due to recurrence. Meshes have limited role in primary surgery for pelvic prolapse. It is possible that benefits exceed risks in a group of women, but there is no clear evidence which is that group.